Public transport problem in Pasir Gudang Johor / Faris Izhwan Mohamad Rosli - Faris Izhwan, Mohamad Rosli (2020)
This study is about the increasingly poor use of public buses among the residents of Pasir Gudang. Public transport such as public buses are important in creating a viable city with good traffic flow. Pasir Gudang is the largest industrial city in Johor and a case study on the use of public buses should be done. For this study was conducted in three stages, including background study, data collection and analysis and recommendations and conclusions. In this study using non-probability sampling. Populations have the same probability of selection, such as random sampling, or pre-selected probabilities and are used in analysis to assess importance. The total number of target respondents is 32 respondents among public bus users in Pasir Gudang. This study analyzes four main elements namely public bus service, bus travel route, bus scheduling system and public bus frequency. This analysis to determine the satisfaction of respondents on the public bus element in Pasir Gudang. The problems gained from this study will be the main findings and recommendations in this study to improve the more effective public bus element.